Challenging Management of Wound Infection with Silver Sulfadiazine in a Rural Hospital: a Case Series and Literature Review - Sarah Saniyyah As’ad; Iswinarno Doso Saputro; Halbana Al Maududy; Kartika Ayu Pranindita (Eduvest - Journal of Universal Studies, 2026)
Management strategies for wound infection remain a challenge, especially in a rural hospital with limited medical resources, such as West Bangka Hospital. We present three cases of patients with wound infections of varying ages. The first case involved a newborn who developed an infected wound on the left foot at a previous intravenous cannulation site after two weeks of hospitalization. Silver sulfadiazine was applied topically to the wound once daily and dressed with gauze. Within three days, oedema and purulent discharge had diminished, and no adverse effects were observed. The second and third cases involved a fifty-year-old man with a history of diabetes who had an infected wound on his right foot for a few days, and a sixty-three-year-old man with a wound infection on his left buttock due to prolonged bed rest. Silver sulfadiazine was applied to the wound and dressed with gauze. Following the application, no adverse reactions were observed. Both patients didn’t undergo follow-up or documentation. Our review shows that silver sulfadiazine exhibits bactericidal activity against both Gram-positive and Gram-negative bacteria and positively influences wound healing by modulating zinc levels and inflammatory cytokine production. The silver cream component constantly absorbs exudates, maintaining the wound in moist conditions. Silver sulfadiazine is commonly used to treat burn wounds due to its cost-effectiveness, tolerability, and safety. Silver sulfadiazine can be an effective treatment for the management of wound infections in newborns and adults, especially in a rural hospital with limited medical resources.